Judging the Masses: Spectatorship, Action, and Politics in Arendt’s Critique of the Masses - Zeldes-Roth, Miko (HannahArendt.net, 2024)
This paper focuses on Arendt’s treatment of the masses and uses Arendt’s methodological commitments to contingency and intersubjectively constituted truth-claims to read against her own overdetermined conclusions about the antipolitical fate of the masses. Drawing on Arendt’s own appraisals of certain episodes of mobilization and revolutionary politics, most notably the Hungarian Revolution, this paper shows how masses are not inherently sites of depersonalization as Arendt claims. Rather, masses can allow for the individual appearance, action, and judging that Arendt herself frames as the foundation of freedom and politics. This paper distinguishes between masses as an historical reality as opposed to a representative term, showing how Arendt’s commitment to the former obscures both the diverse array of street politics that she reduces into the masses and how her conclusions rely upon her own subjective judgments. As quintessentially public events and spaces, masses are shaped by the judgments of both those within and outside the mobilization in question. Turning to Arendt and Linda Zerilli’s theories of judging, this paper emphasizes how judging is a practice which can define masses as political (or not). This does not mean that there are no evaluative standards with which to differentiate mobilizations. Rather, this paper shows how Arendt’s theory is flexible enough to recover a more contingent, political reading of masses without collapsing distinctions between antidemocratic and democratic mobilizations.